2004
DOI: 10.1086/377714
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Measles among Unvacdnated Young Adults and Measles Seroprevalence Study: Implications for Measles Outbreak Control in Adult Populations

Abstract: Measles incidence has declined significantly in the United States since the 1989-1991 resurgence. Several conditions, including pockets of underimmunization, international importation, and the inability to rapidly detect and contain cases, represent potential threats to this success. During the 1995-1996 winter holiday season, the Minnesota Department of Health investigated an outbreak of measles among unvaccinated young adults affiliated with a religious community. A total of 26 outbreak-associated cases of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Parker et al [30] reported an outbreak of 43 cases in Indiana in 2005; the rate of vaccination coverage among the schoolchildren was 98%. Ehresmann et al [31] described a similar phenomenon. In The Netherlands, where the national rate of coverage is 96%, an outbreak in 1999 caused almost 3000 cases among people who rejected vaccination for religious reasons [11].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Parker et al [30] reported an outbreak of 43 cases in Indiana in 2005; the rate of vaccination coverage among the schoolchildren was 98%. Ehresmann et al [31] described a similar phenomenon. In The Netherlands, where the national rate of coverage is 96%, an outbreak in 1999 caused almost 3000 cases among people who rejected vaccination for religious reasons [11].…”
Section: Discussionmentioning
confidence: 82%
“…As Orenstein et al [40] suggest, it is difficult to believe that adult patients can sustain a transmission chain in the general population. Likewise, several authors suggest that, if there are high coverage rates among schoolchildren, it is difficult for the outbreak to propagate in the community, even if there are susceptible adults [30,31]. Therefore, we consider high rates of coverage with 2 vaccine doses for children to be essential, and the rates should be distributed homogeneously, avoiding pools of susceptible children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after such extensive WHO-EPI program for measles eradication, these programs never reach 100% of the population and this leads to the disease resurgence. In the recent past, there was a resurgence of measles with confirmed cases reported in various countries and regions worldwide making this a global problem [5][6][7][8][9][10]. In the southern Africa, the resurgence of measles virus infection accompanied with high HIV prevalence makes measles diagnosis and treatment of high importance [4, 13,49,50].…”
Section: Human and Newborn Calf Sera Studiesmentioning
confidence: 99%
“…Eastern and southern African countries have recently reported the resurgence of measles outbreaks with 200,000 confirmed cases and 1400 recorded deaths according UNICEF/WHO [2,3] and Centers for Disease Control and Prevention [4]. Confirmed measles cases have also been reported in various countries and regions worldwide making this a global problem [5][6][7][8][9][10]. South Africa has recently experienced various disease outbreaks, such as rift-valley fever (a zoonotic disease) with 13,902 confirmed animal cases (8581 deaths) [11] and measles with 417,000 confirmed human infected cases [11][12][13].…”
Section: Introductionmentioning
confidence: 99%